2007
DOI: 10.1074/jbc.m705298200
|View full text |Cite
|
Sign up to set email alerts
|

Gp120 V3-dependent Impairment of R5 HIV-1 Infectivity Due to Virion-incorporated CCR5

Abstract: Entry of R5 human immunodeficiency virus type 1 (HIV-1) into target cells requires sequential interactions of the envelope glycoprotein gp120 with the receptor CD4 and the coreceptor CCR5. We investigated replication of 45 R5 viral clones derived from the HIV-1 JR-FLan library carrying 0 -10 random amino acid substitutions in the gp120 V3 loop. It was found that 6.7% (3/45) of the viruses revealed >10-fold replication suppression in PM1/CCR5 cells expressing high levels of CCR5 compared with PM1 cells expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Proteomics studies showed that a large number (ϳ100) of cellular proteins associated with the plasma membrane are incorporated into HIV-1 particles released by infected macrophages (21). However, the specific molecular mechanisms that mediate incorporation of host membrane proteins into virions remain largely unexplored, except for those for BST-2/tetherin (22) and virus receptors (23)(24)(25). This is in contrast to the incorporation of viral glycoproteins, where several mechanisms have been investigated (26,27).…”
mentioning
confidence: 60%
“…Proteomics studies showed that a large number (ϳ100) of cellular proteins associated with the plasma membrane are incorporated into HIV-1 particles released by infected macrophages (21). However, the specific molecular mechanisms that mediate incorporation of host membrane proteins into virions remain largely unexplored, except for those for BST-2/tetherin (22) and virus receptors (23)(24)(25). This is in contrast to the incorporation of viral glycoproteins, where several mechanisms have been investigated (26,27).…”
mentioning
confidence: 60%
“…In total, we cloned 31 different V3 sequences from 30 individuals, of which 14 (45.2%) were below the 5% FPR cutoff, suggesting a high frequency of CXCR4 usage in this area (Table 1). To confirm coreceptor usage using phenotypic assays, we produced luciferase reporter HIV-1 pseudotyped with Env that carried each V3 region in its strain JR-FL background (38,39). We used these viruses to infect NP-2/CD4 cells that expressed either CCR5 or CXCR4 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The amplified fragment carrying the AflII and NheI sites was cloned into a pCR-TOPO vector (Invitrogen) and sequenced. The AflII-NheI-carrying fragment of the V3 region was then introduced into the AflII-NheI cloning site of the pCXN-FLan vector as previously described (39,75). A luciferase reporter HIV-1 pseudotyped with Env carrying the V3 region or full-length Env was prepared by transfecting 293T cells with pNL-LucΔBglII and each Env expression vector (25,38,(75)(76)(77).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that the incorporation of larger amounts of HIV-1 coreceptor CCR5 into virions impaired the infectivity of HIV-1 when a CCR5-high CD4 ϩ T-cell line was infected with a distinct HIV-1 molecular clone, while a CCR5-low CD4 ϩ T-cell line was able to support virus infectivity (42). Because primary CD4…”
Section: Discussionmentioning
confidence: 99%